Modification of Food Systems by Ultrasound - L. M. Carrillo-Lopez; A. D. Alarcon-Rojo; L. Luna-Rodriguez; R. Reyes-Villagrana (Journal of Food Quality)
This review describes the mechanism, operation, and recent potential applications of ultrasound in various food systems, as well as the physical and chemical effects of ultrasound treatments on the conservation and modification of different groups of food. Acoustic energy has been recognized as an emerging technology with great potential for applications in the food industry. The phenomenon of acoustic cavitation, which modifies the physical, chemical, and functional properties of food, can be used to improve existing processes and to develop new ones. The combination of ultrasonic energy with a sanitizing agent can improve the effect of microbial reduction in foods and, thereby, their quality. Finally, it is concluded that the use of ultrasound in food is a very promising area of research; however, more research is still needed before applying this technology in a wider range of industrial sectors.